(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Date fruits arrive in the high-humidity southern Nigerian market in a dried state and are highly hygroscopic. Some engineering properties (EP) relevant to the design of handling, processing, and storage equipment for this hygroscopic dried fruit were studied as a function of moisture content. The EP determined were: length, width, and thickness (L, W, T); geometric mean diameter (Dg); arithmetic mean diameter (Da); square mean diameter (Ds); equivalent mean diameter (De); surface area (S); aspect ratio (AR); specific surface area (Ss); sphericity (φ); mass (M); volume (V); density (D); porosity (ε); angle of repose (ζ); and coefficient of static friction (CoF) on three structural surfaces — glass (CoFg), plywood (CoFp), and galvanised steel (CoFgs) — at five moisture content levels (MCL) ranging from 6.08 to 16.23% (wet basis). Each EP was evaluated on 500 replicates, comprising 100 replicates per MCL. All measurements followed standard procedures reported in the literature. Mean values (±SD) were: L = 35.47 ± 3.40 mm; W = 17.53 ± 1.65 mm; T = 15.65 ± 1.53 mm; Dg = 21.32 ± 1.69 mm; Da = 22.88 ± 1.85 mm; Ds = 21.98 ± 1.75 mm; De = 22.06 ± 1.76 mm; S = 20257.69 ± 4864.71 mm²; AR = 0.496 ± 0.044; Ss = 6.03 ± 1.60 mm²/ml; M = 6.03 ± 1.60 g; V = 6.43 ± 1.60 cm³; D = 0.94 ± 0.06 g cm⁻³; ε = 40.42 ± 3.93%; ζ = 35.35 ± 2.82°; CoFg = 0.357 ± 0.047; CoFp = 0.338 ± 0.070; and CoFgs = 0.268 ± 0.034. All EP increased with increasing moisture content, with the exception of ζ, which showed an inverse relationship until the penultimate MCL before rising at 16.23%. Analysis of variance confirmed that the effect of moisture content was statistically significant (p ≤ 0.05) for thickness, density, porosity, and CoF on all three surfaces. CoFp exhibited the highest values at all MCL studied. The results of this study are intended to support food engineers and processing equipment designers working with dried date fruits.